The Relationship between Drinking Coffee and Hypertension in Several Countries: Systematic Review and Meta-Analysis - Syarif, Syahrizal; Mivtahurrahimah, Mivtahurrahimah (JURNAL INFO KESEHATAN, 2024)
Coffee is the most consumed drink in the world and has the highest caffeine content. Caffeine in coffee has an effect on hypertension, which is a leading cause of death throughout the world. However, the long-term effect of drinking coffee on the risk of hypertension is still controversial. This study aimed to determine the relationship between drinking coffee and the risk of hypertension through a meta-analysis study of several cross-sectional survey studies using the search engines PubMed, Science Direct, Proques, and Scopus. Search results via search engines found 3 relevant articles for analysis. A significant association was found between drinking coffee and hypertension with a combined risk of 1.58 (95% CI: 1.46, 1.72). Lifestyle changes through regulating coffee drinking patterns can be one of the government and stakeholder programs as primary prevention of hypertension among adults, especially since drinking coffee is currently very popular.